2014
DOI: 10.1186/1472-6947-14-1
|View full text |Cite
|
Sign up to set email alerts
|

In eHealth in India today, the nature of work, the challenges and the finances: an interview-based study

Abstract: BackgroundIndia is a country with vast unmet medical needs. eHealth has the potential to improve the quality of health care and reach the unreached. We have sought to understand the kinds of eHealth programmes being offered in India today, the challenges they face and the nature of their financing.MethodsWe have adopted an interview-based methodology. The 30 interviews represent 28 organizations, and include designers, implementers, evaluators and technology providers for eHealth programmes.ResultsA range of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 25 publications
(32 reference statements)
2
75
0
Order By: Relevance
“…This findings corresponds to those published in other studies. For example, Qureshi et al (2013), Hoque, Mazmum & Bao (2014) and Jaroslawski & Saberwal (2014) identified some challenges affecting the adoption and utilization of ICT tools in hospitals, which include poor user acceptance, lack of infrastructure, financial constraints, lack of computer literacy, and organizational policies.…”
Section: Discussionmentioning
confidence: 99%
“…This findings corresponds to those published in other studies. For example, Qureshi et al (2013), Hoque, Mazmum & Bao (2014) and Jaroslawski & Saberwal (2014) identified some challenges affecting the adoption and utilization of ICT tools in hospitals, which include poor user acceptance, lack of infrastructure, financial constraints, lack of computer literacy, and organizational policies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study appear to indicate that investing in health centres’ ICT might prove to be one very important avenue for boosting retention of health workers in rural areas. In order for ICT to influence retention positively, there is need to train health workers [32]. Further, increasing the presence of ICT in rural health centres will likely improve retention and availability of health workers in rural areas including those in rural post-war conflict situations.…”
Section: Discussionmentioning
confidence: 99%
“…These current barriers need to be addressed directly by making ICT intervention one of the priority strategies in the plan for the reconstruction of post-war conflict situations. Massive training and investment in ICT facilities by government and other development partners based on the needs of health workers should be considered as a priority [32]. If ICT is to improve health workers’ retention as aforementioned, then the elimination of the identified barriers should be one of the immediate steps to take in encouraging or fostering retention of health workers in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…the government [33] indirectly affect the quality of service that healthcare providers can provide to their patients. A further problem, agreeing on reimbursement [24], can be a challenge for new technologies especially as they are of unproven value [7] as well as when some technologies are initially viewed as too expensive to integrate into everyday clinical practice [31]. The literature, therefore highlights the need to improve cost-effectiveness and avoid initiatives, which are considered as wasteful [32].…”
Section: Challengesmentioning
confidence: 99%